ENHANCING EDUCATIONAL EXCELLENCE: THE ART OF ORGANIZING THE PEDAGOGICAL PROCESS IN HIGHER EDUCATION - Bekmuratov Kadirbergen Kuuanishbayevich (Journals Park Publishing, 2023)
The organization of the pedagogical process in higher education is a complex yet integral facet of fostering academic excellence and student success. As universities and colleges strive to meet the evolving needs of diverse student bodies, the structure and management of the pedagogical process become paramount. This article delves into the intricacies of organizing the pedagogical process in higher education, exploring key components, innovative strategies, and the broader implications for shaping the educational landscape.
Keywords: Pedagogical process, Higher education, Curriculum design, Instructional methods, Assessment strategies, Faculty development, Technological integration, Student-centric approach, Inclusivity, Global perspectives, Interdisciplinary collaborations.